Dietary Variety Impairs Habituation in Children - Temple, Jennifer L. (2008)
OBJECTIVE: The purpose of these studies was to test the hypothesis that dietary variety decreases the rate of habituation and increases energy intake in children. DESIGN: In Experiment 1, salivation in response to the same or a variety of food cues was measured followed by consumption of the study food(s). In Experiment 2, children responded in a computer task to earn points for the same or a variety of low or high energy density foods, which were then consumed. MAIN OUTCOME MEASURES: Salivation, number of responses, and energy intake were measured. RESULTS: Participants in the same groups habituated faster than those in the variety groups (p < .05), and in Experiment 2, the effect of variety was independent of energy density. Participants in the variety groups also consumed more energy than those in the same groups in both experiments (p < .05). CONCLUSIONS: Dietary variety disrupted habituation and increased energy intake in children. In addition, the response to dietary variety was independent of energy density, suggesting that increasing variety of low energy density foods may increase consumption.